Reseña de Tasnim ABDERRAHIM, Laura-Theresa KRUGER, Slama BESBES y Katharina MCLAURREN (eds.) (2017): Tunisia’s International Relations since the Arab Spring: Transition Inside and Out, Routledge, London?New York - Govantes, Bosco (Revista de Estudios Internacionales Mediterráneos, 2018)
Bosco GOVANTES (2018), Reseña de Tasnin ABDERRAHIN, Laura-Theresa KRÜGER, Salma BESBES y Katharina McLARREN (eds) (2018), Tunisia’s International Relations since the ’Arab Spring’: Transition Inside and Out, Routledge, London?New York en Revista de Estudios Internacionales Mediterráneos